Pengaruh Kebijakan Insentif Pajak Penghasilan Bagi UMKM dan Digitalisasi Pajak Terhadap Kepatuhan Wajib Pajak - Ria Dwi Apriliana; Juli Ratnawati (El-Mal: Jurnal Kajian Ekonomi & Bisnis Islam, 2025)
Tax plays an important role as a source of state revenue. Therefore, the government sets the obligation to pay taxes for the community as part of its responsibility. Significant technological developments and global economic uncertainty have made digitalization and tax incentives the main factors in MSME taxpayer compliance. Tax digitalization aims to increase transparency, while tax incentives are carried out to reduce the tax burden on MSMEs in order to increase taxpayer compliance. This study aims to determine the effect of tax incentives and digitalization on MSME taxpayer compliance. The methodology used is multiple linear regression analysis using 100 MSME samples in Semarang. The results of the study show that tax incentives have an effect on MSME taxpayer compliance, based on the results of the t or partial test, which shows a significant value (X1) or the tax incentive variable obtained a result of 0.029 < 0.05, and the t-count is greater than the t-table (2.217 > 1.6607). Furthermore, tax digitalization has an influence on taxpayer compliance of MSMEs, by showing the results of the T-test or partial where the significant value of the tax digitalization variable (X2) is 0.00 < 0.05 and the t-count value obtained the result (6.161 > 1.6607).